Microsatellite instability in early onset and familial colorectal cancer. Issue 12 (December 1996) - Brassett, C; Joyce, J A; Froggatt, N J; Williams, G; Furniss, D; Walsh, S; Miller, R; Evans, D G; Maher, E R
Abstract : Hereditary non-polyposis colorectal cancer syndrome (HNPCC) is often considered to be the most common form of inherited colorectal cancer, although its precise incidence is unknown. The clinical diagnosis of HNPCC relies on a combination of family history and young age of onset of colorectal cancer, but as many familial aggregations of colorectal cancer do not fulfil the strict diagnostic criteria, HNPCC might be underdiagnosed. The majority of HNPCC families have germline mutations in mismatch repair (MMR) genes, such as MSH2 or MLH1, so that HNPCC cancers characteristically exhibit DNA replication errors (RERs) at microsatellite loci. Although an RER positive phenotype in tumours can also result from somatic mutations in an MMR gene, the prevalence of RER + tumours should provide a maximum estimate of the incidence of germline MMR gene mutations in patients with early onset and familial colorectal cancer. We investigated colorectal cancers for RERs from (1) a population based study of 33 patients with colorectal cancer aged 45 years or less, (2) 65 kindreds with familial colorectal cancer which only partially fulfilled the criteria for the diagnosis of HNPCC, and (3) 18 cancers from 12 HNPCC kindreds. Seven of 33 patients (21%) with colorectal cancer aged 45 years or less had an RER + cancer, with only two of these having a clear family history of HNPCC. A greater proportion of RER + tumours (5/7) occurred proximal to the splenic flexure than RER - tumours (4/26; chi2 = 6.14, p < 0.025). RERs were detected in all 18 cancers from HNPCC patients but in only six of 65 non-HNPCC familial colorectal cancer kindreds (9%; chi2 = 52.2, p < 0.0005). These findings suggest that most cancers in patients diagnosed at 45 years of age or less and familial aggregations of colorectal cancer which do not fulfil HNPCC diagnostic criteria do not have germline mutations in MSH2 and MLH1. Hence population screening for germline mutations in these genes is unlikely to be an efficient strategy for identifying people at high risk of developing colorectal cancer.